TRADITIONAL ECOLOGICAL KNOWLEDGE AND MARINE PROTECTED AREAS: CREATING AN INTEGRATIVE MODEL WITHIN THE BLUE ECONOMY FRAMEWORK - Molan, Kristianus Simon Hale (Sosiohumaniora, 2026)
This manuscript examines the role of traditional ecological knowledge as a foundation for the reconfiguration of marine protected area towards greater equity and effectiveness. Utilizing an analytical framework that integrates political ecology, TEK, and co management, this study critiques power relations in marine resource management and proposes an adaptive and inclusive governance model rooted in recognition, the redistribution of authority, and the institutionalization of local knowledge as an equal legal and scientific basis. Findings indicate that the success of marine conservation area management depends on governance capacity to bridge top down and bottom up approaches, ensure equitable benefit distribution, and foster local community participation and recognition through the integration of local wisdom. Nevertheless, implementation requires a committed effort to overcome capacity constraints, budgetary limitations, and institutional fragmentation. Recommendations for an adaptive and progressive governance model include:(1) recognizing TEK as a legal and scientific basis for conservation area management;(2) participatory mapping and institutional integration to transform indigenous knowledge into inclusive policy;(3) implementing substantive co-management with the redistribution of power to indigenous communities as decision makers;(4) legal harmonization that acknowledges customary sanctions as part of regulatory enforcement; and (5) participatory adaptive evaluation to ensure responsiveness to socio ecological dynamics and equitable benefit sharing.